Redefining of the concept of a migrant housemaid in Ali's Minah Tetap Dipancung - Iskarna, Tatang (Diksi, 2022)
This article explores diasporic problems faced by an Indonesian migrant housemaid working in Saudi Arabia, presented in Denny J. Ali's essay poem "Minah Tetap Dipancung" or "Minah is determined to be beheaded" (2012). This article uses diasporic literary criticism and poetry explication to reveal her tricky situation, struggle against oppression, and voice of hope concerning her profession. The analysis shows that Minah experiences disillusionment. She is oppressed, abused, and alienated because of the cultural barrier. However, Minah resists class and gender-based subjugation. Although she is helpless and determined to face the death sentence, she stands for her dignity. This poem also voices the need to redefine the concept of a migrant housemaid. Government and migrant worker stakeholders should set political will for improving the condition of migrant woman workers, especially legal protection, advocacy, and treatment as professional workers free from cultural bias in the destination country. A migrant housemaid is not merely an informal and private worker that the employer can treat as property arbitrarily. This poem advocates redefining her as a professional worker viewed from a broader cultural perspective, protected before the law, and provided with appropriate rights and advocacy. Keywords: migrant worker, diasporic problems, diasporic literary criticism, class-gender subjugation